Cultural Issues in Conducting Interview in Qualitative Research: Guidance for Novice Researchers - Joungtrakul, Jamnean; Someran, Laddawan; Pokateerakul, Pakamon; Salapsri, Sureeporn (Journal of Multidisciplinary Academic Research and Development (JMARD), 2024)
This academic article aims at presenting cultural issues in conducting interview in qualitative research. A non-systematic literature review is applied in this study. A review of related literature is conducted and data extraction is performed and used as a basis for composing this article. The scope of this article comprises: (1) background and significance of the topic to be studied plus objective, method and scope of the study; (2) literature review on definition, types of interview process and cultural issues in interview in qualitative research; (3) conclusion and discussion: The study identifies seven cultural issues that researcher should take into consideration in conducting interview in qualitative research comprised: Paralinguistics; Proxemics; Gender; Status; Timing; Religious; and Ethnicity. Furthermore, to enhance research validity, various data verification methods should be employed when examining and interpreting interview data; (4) new findings from the study: A model of cultural considerations in qualitative research interviews has been developed. This model serves as a comprehensive guideline for conducting interviews, emphasizing seven key cultural issues to ensure high-quality data collection and credible outcomes; and (5) recommendations: It is suggested that future studies explore the ethical dimensions and professional codes of conduct for researchers in relation to interviewing in qualitative research.